2016
DOI: 10.13187/ejced.2016.15.173
|View full text |Cite
|
Sign up to set email alerts
|

Preferences and Attitudes for Using Interactive Whiteboards in Different Courses and Learning

Abstract: The purpose of the study is to investigate teachers' and students' considerations, preferences, attitudes and awareness related to using Interactive Whiteboards in 7-12 grades and different courses, and learning. 1013 students from elementary and secondary schools and 65 teachers from different schools were selected to take questionnaire for defining their preferences and awareness for using IWBs in teaching and learning processes. Descriptive statistical analyses were used to investigate whether there were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
3
0
2
Order By: Relevance
“…Öğretim elemanlarının ve öğretmen adaylarının bir yıllık ET kullanma deneyimleri sonrasında kendilerinden elde edilen verilerin çözümlenmesi sonucunda öğretim elemanlarının ve öğretmen adaylarının ET ile ilgili görüşlerinin genel olarak olumlu olduğu söylenebilir. Alanyazında bu durumu destekleyen birçok çalışma bulunmaktadır (Badilla Quintana, 2012;Bakadam & Asiri, 2012;Bidaki & Mobasheri, 2013;Divaharan & Koh, 2010;Emeagwali & Naghdipour, 2013;Gadbois & Haverstock, 2012;Gregory, 2010;Ipek & Sözcü, 2016). Bu çalışmaların çoğunda ET ile ilgili öğrenci ve öğretmenlerin görüş ve düşüncelerine yer verilmiş; ET kullanma oranı ve niteliğine bağlı olarak bu görüş ve düşüncelerin artış gösterdiği belirtilmiştir.…”
Section: Tartışma Ve Sonuçunclassified
See 1 more Smart Citation
“…Öğretim elemanlarının ve öğretmen adaylarının bir yıllık ET kullanma deneyimleri sonrasında kendilerinden elde edilen verilerin çözümlenmesi sonucunda öğretim elemanlarının ve öğretmen adaylarının ET ile ilgili görüşlerinin genel olarak olumlu olduğu söylenebilir. Alanyazında bu durumu destekleyen birçok çalışma bulunmaktadır (Badilla Quintana, 2012;Bakadam & Asiri, 2012;Bidaki & Mobasheri, 2013;Divaharan & Koh, 2010;Emeagwali & Naghdipour, 2013;Gadbois & Haverstock, 2012;Gregory, 2010;Ipek & Sözcü, 2016). Bu çalışmaların çoğunda ET ile ilgili öğrenci ve öğretmenlerin görüş ve düşüncelerine yer verilmiş; ET kullanma oranı ve niteliğine bağlı olarak bu görüş ve düşüncelerin artış gösterdiği belirtilmiştir.…”
Section: Tartışma Ve Sonuçunclassified
“…Öğretmenlerin doğru pedagojik yaklaşımlarla yeni teknolojileri sınıflarında kullanmaları bu süreçlerin amaçları doğrultusunda gerçekleşmesinde önemli bir etken olarak görülebilir (Badilla Quintana, 2012;Beauchamp & Kennewell, 2012;Canbolat, 2011;Shulman, 1986;Sumak & Sorgo, 2016;Yüksel & Adıgüzel, 2012). Bununla beraber yeni neslin teknoloji kullanımına yönelik ilgi ve becerileri öğretmenlerinin de onların eğitim sürecine etkin katılımlarını sağlamak (Ali & Al-kaabi, 2012;Badilla Quintana, 2012;Bruffaerts-Thomas & Bruffaerts, 2013;Ipek & Sözcü, 2016;Lopez & Krockover, 2014;Tataroglu & Erduran, 2010;Winzenried, Dalgarno & Tinkler, 2010) adına yeterli düzeyde teknoloji kullanabilme yetisine sahip olmalarını gerektirdiği de söylenebilir (Akgün, 2013;Lai, 2014;Shulman, 1986). Ayrıca eğitim sürecinde teknoloji kullanımına yönelik öğretmen yetiştirme sürecine de dikkat çekilerek; teknolojiden beklenen yararın elde edilebilmesi için öğretmen adaylarının uygun teknolojileri uygun pedagojik yaklaşımlarla kullanabilecek ve bu yetilerini öğrencilerine de aktarabilecek şekilde yetiştirilmeleri gerektiği vurgulanmaktadır (Beauchamp & Kennewell, 2012;Campbell & Martin, 2010;Çelik & Kahyaoğlu, 2007;Mishra & Koehler, 2006;Schmidt vd., 2009;Sumak & Sorgo, 2016;Winzenried vd., 2010).…”
Section: Introductionunclassified
“…The study indicated that both teachers and students had positive attitudes towards IWBs and that the IWBs provided motivation and in-class participation. İpek and Sözcü (2016) carried out a descriptive study on the preferences and attitudes of students and teachers towards the use of IWBs in grades 7-12. In the study, student and teacher questionnaires were used to examine participants' attitudes, preferences, awareness, and consideration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…İpek & Sözcü, 2016;Wong & Goh, 2015). Some particular definitions highlighted the main characteristics of IWBs including their "large interactive display" (İpek & Sözcü, 2016), carrying an "electronic touchable whiteboard" (Al-Qirim, 2014) and having "touch-sensitive interactive display" (Öz, The New Generation of Interactive Whiteboards: How Students Perceive and Conceptualize? F. Saltan Participatory Educational Research (PER) -94-2014).…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that teachers and students generally have positive attitudes towards the use of IWBs in schools (İpek & Sözcü, 2016;Akgün &;Balta & Duran, 2015;Koru-Yücekaya, 2015;Mathews-Aydinli & Elaziz, 2010;Somyürek, Atasoy & Özdemir, 2009). Several benefits of IWBs have been pinpointed in the relevant literature, which can be enlisted as: learner engagement and interactivity (Schmid & Schimmack, 2010;Smith et al, 2005) visual quality, (Sad & Ozhan, 2012;Slay et al, 2008 ) motivation (Higgins, 2010;Yıldız & Tüfekçi ,2012) academic achievement, (Holmes, 2009;İpek& Sözcü, 2016;Yang, Wang, & Kao, 2012;Yorgancı, & Terzioğlu, 2013); knowledge construction (Warwick, Hennessy & Mercer, 2011) and classroom management (İpek & Sözcü, 2016). Some studies found that using IWBs in the classroom increased students' achievement levels in mathematics and science (Akgün & Koru-Yücekaya, 2015;Bulut, & Koçoğlu, 2012;Swan & Marshall,2010).…”
Section: Introductionmentioning
confidence: 99%